Śrīviṭhṭhala āṇi kshetra Paṇḍharapūra : sãśodhanātūna - Mañjūḷa, Vā. La. (Vāsudeva Lakshmaṇa), 1935- (Puṇe : Utkarsha Prakāśana, 2018)
On the cult of Viṭhṭhala, Hindu deity.
In Marathi.
Keywords: Viṭhṭhala -- (Hindu deity) -- Cult; Pandharpur (India) -- Religious life and customs; Hindu pilgrims and pilgrimages -- India -- Pandharpur; Vārkarī sect -- India -- Maharashtra -- History; Cults; Hindu pilgrims and pilgrimages; Vārkarī sect; India -- Maharashtra; India -- Pandharpur; History